SPE Eastern Regional/Aapg Eastern Section Joint Meeting 2008
DOI: 10.2118/117236-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water-Production Diagnosis Using Transient Test With Multiphase Flowmeter

Abstract: Accurate determination of oil, water, and gas production rates is an important element of oilfield management and optimization. Multiphase flow meters (MPFM) are being accepted more and more for well testing, reservoir management, production allocation, production monitoring, and fiscal metering. In addition to common MPFM applications, this study shows how a multiphase flow meter may be used as a valuable tool to evaluate water production problems of the well by imposing transient flowing conditions to the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Analytical and empirical procedures in view of production information make up the second category. In view of the characteristics of the reservoir and the fluid, other authors have developed less prevalent WPM diagnostic strategies [28][29][30][31]. Traditionally, the production logging tool (PLT) is used to identify water inflow zones when the water cut rises excessively at extreme levels.…”
Section: Page|11mentioning
confidence: 99%
“…Analytical and empirical procedures in view of production information make up the second category. In view of the characteristics of the reservoir and the fluid, other authors have developed less prevalent WPM diagnostic strategies [28][29][30][31]. Traditionally, the production logging tool (PLT) is used to identify water inflow zones when the water cut rises excessively at extreme levels.…”
Section: Page|11mentioning
confidence: 99%
“…The second group consists of various analytical and empirical techniques based on production data. There are also other less common techniques proposed by different authors for WPM diagnostics based on reservoir and fluid characteristics (Novontny 1995;Egbe and Appah 2005;Gasbarri et al 2008;Ayeni 2008), which we will discuss in brief later in section 2.2.3.…”
Section: Conventional Tools and Techniques For Wpm Diagnosismentioning
confidence: 99%
“…They concluded that wells with coning problem represented periodic spectrums with narrow spectral width. Gasbarri et al (2008) proposed a diagnosis technique using transient test and multiphase flow meters. They used reservoir simulations to build three base cases of WPM models of coning, water channelling and flow behind casing.…”
Section: Limitations Of Conventional Wpms Diagnostic Techniquesmentioning
confidence: 99%
“…Therefore, the locus of the balance point is a stable cone shaped water oil interface. At this stable situation oil flows above the interface while water remains stationary below the interface (Gasbarri et al, 2007).…”
mentioning
confidence: 98%
“…source of such problems must be identified in order to apply effective and suitable techniques to control water production (Gasbarri et al, 2007). The cause of water coning is an imbalance between the viscous and gravitational forces around the completion interval.…”
mentioning
confidence: 99%